1997
DOI: 10.1006/qres.1997.1893
|View full text |Cite
|
Sign up to set email alerts
|

Eolian Quartz Flux to Lake Biwa, Central Japan, over the Past 145,000 Years

Abstract: Eolian quartz flux (EQF, g cm−2(103 yr)−1) to Lake Biwa, central Japan, provides direct information on variations of the East Asian winter monsoon. Lake Biwa sediments spanning the past ca. 145,000 yr are characterized by two main periods when EQF values were significantly greater than 5.50 g cm−2(103 yr)−1, and two main intervals during which EQF values were lower. Two periods with EQF values >5.50 g cm−2(103 yr)−1occurred from ca. 145,000 to 125,000 and 73,000 to 13,000 yr B.P., while times of lower EQF v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 37 publications
1
42
0
1
Order By: Relevance
“…7c) (Xiao et al, 1995) because the grain size of quartz particles eliminates pedogenic effects and serves as a reliable proxy for winter monsoon strength (Sun et al, 2006a,b). Evidence of Asian dust has been found down wind, far from the dust source area in western China, in Japan (Xiao et al, 1997) and in deep-sea sediments across a wide section of the North Pacific Ocean (Hovan et al, 1989(Hovan et al, , 1991Rea, 1990). Variation of dust records in the marine core V21-146 from northwestern Pacific (Fig.…”
Section: Temporal and Spatial Variation Of Winter Monsoon Intensity Dmentioning
confidence: 95%
“…7c) (Xiao et al, 1995) because the grain size of quartz particles eliminates pedogenic effects and serves as a reliable proxy for winter monsoon strength (Sun et al, 2006a,b). Evidence of Asian dust has been found down wind, far from the dust source area in western China, in Japan (Xiao et al, 1997) and in deep-sea sediments across a wide section of the North Pacific Ocean (Hovan et al, 1989(Hovan et al, , 1991Rea, 1990). Variation of dust records in the marine core V21-146 from northwestern Pacific (Fig.…”
Section: Temporal and Spatial Variation Of Winter Monsoon Intensity Dmentioning
confidence: 95%
“…An alternative method of deciphering the eolian record is to examine the wind-blown component of lacustrine sediments. In both midcontinental North America (Dean, 1997) and Asia (Xiao et al, 1997), investigators have demonstrated that, under favorable circumstances, it is possible to obtain long and detailed eolian records from lake sediments. Furthermore, unlike loess deposits, which are subject to either erosion (resulting in incomplete records) or colluvial reworking (resulting in mixed stratigraphy), lacustrine records typically contain few or no unconformities and usually contain sufficient organic matter for radiocarbon dating at multiple intervals.…”
Section: Introductionmentioning
confidence: 99%
“…1.0 cal ka BP in the desert/loess transition areas. Thus, the Cheju EQF record suggests that longterm variability in eolian dust deposition in downwind areas has been controlled by the aridity of source areas and winter monsoon strength during the mid-to late (Xiao et al 1997) with the benthic δ 18 O record (Lisiecki and Raymo 2005). The yellow shadows mark the periods of strong Asian winter monsoon Holocene.…”
Section: Asian Winter Monsoon Variabilitymentioning
confidence: 96%
“…The EQF record from Lake Biwa was correlated with records of benthic δ 18 O (Fig. 3.11) and grain-size of the quartz fraction in Chinese loess, implying that the East Asian winter monsoon strengthened during periods when EQF values were high, and weakened during intervals with low EQF values (Xiao et al 1997). However, the EQF record apparently lags ca.…”
mentioning
confidence: 95%